PENGARUH PENDIDIKAN GIZI DENGAN MEDIA BOOKLET TERHADAP PERUBAHAN PERILAKU REMAJA TERKAIT PENCEGAHAN KEKURANGAN ENERGI KRONIS (Studi pada Remaja Putri SMA Kelas XI di SMA Negeri 14 dan SMA Negeri 15 Kota Semarang) - Prastika Yulianasari; Sri Achadi Nugraheni; Apoina Kartini (Jurnal Kesehatan Masyarakat, 2019)
Chronic energy deficiency (CED) are still common in adolescent in Indonesia. Nutrition education with booklets is needed in efforts to prevent CED in adolescent. The purpose of this study is to look at the effect of nutrition education using booklet media on changes in adolescent behavior related to CED prevention. This type of research is Quasy Experimental with pre-post test control group design. The number of samples in each group were 37 students. Samples were taken using a purposive sampling technique in accordance with the inclusion criteria and policies of each school. Nutrition education with booklet media is given to the intervention group for one month starting with socialization at the beginning of booklet distribution. Data analysis used Wilcoxon Signed Rank Test, Mann Whitney, Independent T-Test, and Chi Square. In the initial conditions, there were no differences in knowledge, attitudes, energy adequacy levels, and protein adequacy levels in the two groups with p> 0.05. The results showed a difference in knowledge with p = 0.001 and an increase in scores of 2.5 ± 2.87, a difference in the level of energy adequacy with p = 0.001 and an increase of 15.4 ± 19.69%, and a level of protein adequacy with p = 0.007 and an increase of 16.2 ± 25.54% in the intervention group. However, there was no difference in attitude with p = 0.104 despite an increase in score of 0.3 ± 0.93. It can be concluded that the provision of nutrition education using booklet media is quite effective in increasing adolescent knowledge and practices in efforts to prevent CEDs in adolescents. However, less effect on changes in adolescent attitudes. The suggestion of this study is that teenagers, especially young women can improve the quality and quantity of nutrient intake, especially energy and protein sources.